2019
DOI: 10.6065/apem.2019.24.4.220
|View full text |Cite
|
Sign up to set email alerts
|

Perirenal and epicardial fat and their association with carotid intima-media thickness in children

Abstract: Recent data suggest that subclinical atherosclerosis is more related to visceral adipose tissue distribution than to overall fat mass. Both perirenal fat and epicardial fat are visceral fat depots surrounding the kidneys and the myocardium, respectively, which can be easily assessed by ultrasound. Their clinical relevance in children is largely unknown. This review describes studies relating perirenal and epicardial fat to cardiovascular disease or carotid intima-media thickness (cIMT), a well-established surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
2
12
1
Order By: Relevance
“…Our results also show that in fetuses of 32 weeks of gestation, lobules exhibit a depot-specific architecture with marked fibrous septa, and a morphology similar to that described previously for visceral fat [ 35 ]. In this line, EAT behaves similarly to other adipose tissues such as subcutaneous and visceral AT, in which the progenitor cell subset repartition is different.…”
Section: Discussionsupporting
confidence: 86%
“…Our results also show that in fetuses of 32 weeks of gestation, lobules exhibit a depot-specific architecture with marked fibrous septa, and a morphology similar to that described previously for visceral fat [ 35 ]. In this line, EAT behaves similarly to other adipose tissues such as subcutaneous and visceral AT, in which the progenitor cell subset repartition is different.…”
Section: Discussionsupporting
confidence: 86%
“…The cIMT of a subgroup of these adolescents also showed a positive association with soluble intercellular adhesion molecule 1 [163]. Other authors have observed that in prepuberal children EAT and PAT are better predictors of cIMT than BMI [164]. Similarly, another study found that HOMA-IR and QUICKI, markers of insulin resistance, are independent predictors of cIMT in boys with overweight and obesity, but not in girls.…”
Section: Arterial Thicknessmentioning
confidence: 73%
“…Visceral adipose tissue was considered to be a kind of “ectopic fat” because this fat reservoir was not the usual location of fat storage, compared with subcutaneous adipose tissue. In particular, abdominal visceral adipose tissue was more likely to increase the risk of CVD ( 20 , 21 ). A pediatric study has found a significant association between fat masses (especially intra-abdominal fat) and arterial wall thickness and stiffness in children ( 22 ).…”
Section: Discussionmentioning
confidence: 99%